2021
DOI: 10.1021/acsnano.1c00461
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxide Modified Bone Cement Promoting Osseointegration via Multiple Osteogenic Signal Pathways

Abstract: Poly(methyl methacrylate) (PMMA) bone cement has been widely used in orthopedic surgeries including total hip/knee replacement, vertebral compression fracture treatment, and bone defect filling. However, aseptic loosening of the interface between PMMA bone cement and bone often leads to failure. Hence, the development of modified PMMA that facilitates the growth of bone into the modified PMMA bone cement is key to reducing the incidence of aseptic loosening. In this study, MgAl-layered double hydroxide (LDH) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 69 publications
0
52
0
Order By: Relevance
“…In addition, the results in Fig. 7 c, d demonstrated that the expression levels of p-FAK and p-p38 in the nCS group were both decreased in the presence of specific inhibitors, as demonstrated by Western blotting and the subsequent quantitative analysis, indicating that flower-like nanostructures could activate p-FAK and furthermore activated p-p38, which played a crucial role in osteogenesis [ 54 ]. Considering these results together with the qRT–PCR results, we believe that flower-like nanostructures could enhance cell adhesion and osteogenic differentiation mainly by activating the FAK/p38 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results in Fig. 7 c, d demonstrated that the expression levels of p-FAK and p-p38 in the nCS group were both decreased in the presence of specific inhibitors, as demonstrated by Western blotting and the subsequent quantitative analysis, indicating that flower-like nanostructures could activate p-FAK and furthermore activated p-p38, which played a crucial role in osteogenesis [ 54 ]. Considering these results together with the qRT–PCR results, we believe that flower-like nanostructures could enhance cell adhesion and osteogenic differentiation mainly by activating the FAK/p38 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This modification not only reduced the damage caused by PMMA to osteoblasts due to high polymerization temperature but also released magnesium ions to promote osteogenesis. In addition, the microsphere structure on the surface after lactate dehydrogenase degradation was also beneficial for bone formation (Figure 1) (Wang et al, 2021). In addition, Sharma et al improved PMMA bone cement with amine group-functionalized graphene, which reduced cytotoxicity and improved the toughness of bone cement.…”
Section: Improve Bone Cementmentioning
confidence: 98%
“…An increased ratio of P-p38 to p38 indicates the activation of the p38 MAPK signaling pathway. Reproduced with permission from(Wang et al, 2021).…”
mentioning
confidence: 99%
“…added the active metal component Mg–Al layered double hydroxide (LDH) into PMMA. The micro-CT 3D reconstruction showed that after 2 months surgery the volume of new bone was 2.17- and 18.34-fold greater than that of the PMMA&Collagen-I and PMMA groups, respectively, and its role in inducing bone regeneration was further confirmed by assessing key osteogenic pathways [ 85 ]. Yang et al.…”
Section: Injectable Biomaterials For Spinal Degenerative Diseasesmentioning
confidence: 99%